Detection of the 23-bp nucleotide sequence mutation in retinoid acid receptor related orphan receptor alpha (RORA) gene and its effect on sheep litter size. Issue 1 (1st February 2022) - Yang, Yuta; Hu, Huina; Mao, Cui; Jiang, Fugui; Lu, Xiaofang; Han, Xufei; Hao, Kunjie; Lan, Xianyong; Zhang, Qingfeng; Pan, Chuanying
Abstract: Retinoid acid receptor related orphan receptor alpha ( RORA ) transcribes steroid-related genes to regulate estrogen synthesis. As an important reproductive trait, litter size relates to estrogen synthesis. Therefore, it is important to investigate the association between RORA gene and sheep litter size. In this study, one 23-bp nucleotide sequence mutation was identified in intron 1 of RORA gene in 532 female Australian White Sheep. Moreover, the polymorphic information content (PIC) values of this locus was 0.219. The litter size of ID genotype was significantly better than II genotype and DD genotype in the second born litter size ( p  < 0.05). This loci was related to third born litter size and the ID is the dominant genotype ( p  < 0.05). The association between combined genotypes and average litter size showed that sheep with heterozygote (ID) genotypes had larger lamb than homozygous (DD and II) genotypes. To sum, this study provided theoretical references for the comprehensively research of the function of RORA gene and the breeding of Australian White Sheep. The 23-bp indel variants could be considered as molecular markers for the second and third born litter size of sheep for MAS breeding.